The Desacralization of Cikal Bakal Space in Kauman Neighborhood of Yogyakarta: The Changing of Meaning in City's Traditional Settlement - Subroto, T. Yoyok Wahyu (Pusat Studi Lingkungan Hidup Universitas Gadjah Mada, 2009)
Kauman Yogyakarta is one of the traditional settlement which has a strong cultural and religious background. Up to now, Kauman Yogyakarta stand still against the pressure of the city's modern development. The aims of this research are to know and to understand how the people at this area manage the development of their built environment and what kind of changes has been experienced by the people. The phenomenological method use in this reserach based on Husserlian model, which contains three steps called description reduction, eidetic reduction and transcendental reduction. Include in this peper a brief explanation about the social development in Kauman, Yogyakarta which means as a background knowledge for the researchers. At the last part of the paper, a comprehensive description about the changing of meaning as the cikal bakal space or desacralization of cikal bakal space which is experienced by the local people of Kauman, Yogyakarta has been presented.